The impact of leadership on employee work engagement : Evidence from MNCs operating in Finland - Saviolo, Sofia (My University, 2024)
Due to their complex structure, multinational corporations (MNCs) rely on leaders to foster employee work engagement. In particular, developing a sense of engagement among employees is a strategic tool that MNCs can use to retain the best talents within their organisation, and thus maintain competitiveness in the global market. In this process, leaders have the power to influence employee engagement with their leadership practices, and by building high quality relationships with their employees. Extensive previous literature on this topic has focused on analysing the causal relationships between different leadership styles and employee engagement by considering only employees’ perspective. Therefore, this research aims to understand how leaders influence the work engagement of employees in MNCs, by using a dyadic perspective, so including also the leader's viewpoint, and by grounding on the concept of positive leadership, without distinguishing between different styles. Also, the leader-member exchange (LMX) theory is considered, as theoretical perspective explaining the relationship between leaders and employees. The current study responds to the call for qualitative research in the field, as data were collected from nine semi-structured interviews. Specifically, the sample includes both leaders and employees from three different teams of three MNCs operating in Finland in similar fields. The findings of the research explain the understanding of the concept of engagement and the role of the leader in enhancing it. Firstly, they suggest that both leaders and employees in MNCs have a similar understanding of work engagement, which is initially fostered by the multinational context, and then also by personal and organisational factors. Secondly, results demonstrate that leaders influence engagement both directly and indirectly through leadership, and the leader-member relationship. Specifically, leaders need to provide employees with autonomy and feedback, support their personal and professional needs, set up a positive tone in the team and give example of values and work attitudes, as well as to establish a tailored and equal relationship with each of their subordinates, based on caring interpersonal behaviours, open communication and mutual understanding. As a result, the current study extends previous research with its new perspectives and emerging themes. It also provides practical recommendations that MNCs’ leaders should take to promote employee engagement among their team members.
Keywords: employees; leadership (activity); work engagement; international corporations; fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business